The Study Of Warning Symbol For Mild Allergy Caused By Paracetamol - Abd Rahman, Nor Aziyana; Abd Jamil, Azhar (2014)
The purpose of this paper is to discover the challenges of designing allergy symbol in visual form using pictograms and symbol rather than text. It is also to create effective sign using pictograms and symbol that would immediately warn the patients about the risk and taking immediate action if the reaction occurs. Data input were collected from the interviews, analysis of auxiliary labels and close-ended questions survey that were answered by the public to interpret the meaning of allergy symbol created based on the data of paracetamol symptom provided by the National Pharmaceutical Bureau. This paper created an allergy sign that is suitable to address the adverse reaction caused by paracetamol and developed a few paracetamol legend using pictograms and symbol to provide sufficient warning communication. The limitation of this research is to design and evaluates the allergy symbol of paracetamol as a warning sign. Perhaps, this paper would also help to build the collaborative effort among pharmacovigilance and graphic designers to effectively deliver medical care information.